2018
DOI: 10.3389/fnagi.2018.00004
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Alzheimer’s Disease: From Molecular Mechanisms to Therapeutic Implications

Abstract: Alzheimer’s disease (AD) is the most common cause of progressive dementia in the elderly. It is characterized by a progressive and irreversible loss of cognitive abilities and formation of senile plaques, composed mainly of amyloid β (Aβ), and neurofibrillary tangles (NFTs), composed of tau protein, in the hippocampus and cortex of afflicted humans. In brains of AD patients the metabolism of Aβ is dysregulated, which leads to the accumulation and aggregation of Aβ. Metabolism of Aβ and tau proteins is cruciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
268
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(277 citation statements)
references
References 262 publications
(313 reference statements)
6
268
0
3
Order By: Relevance
“…S2). This result is in line with others, where mTOR is found to participate in memory formation and consolidation, and seems targeted by Aβ42 (Lin et al, 2014;Mueed et al, 2019;Uddin et al, 2018). Thus, mTOR inhibition may be another experimental strategy, independent from PI3K activation, to be considered in future AD studies.…”
Section: Pi3k Mechanisms In Aβ42-induced Synapse Toxicitysupporting
confidence: 91%
“…S2). This result is in line with others, where mTOR is found to participate in memory formation and consolidation, and seems targeted by Aβ42 (Lin et al, 2014;Mueed et al, 2019;Uddin et al, 2018). Thus, mTOR inhibition may be another experimental strategy, independent from PI3K activation, to be considered in future AD studies.…”
Section: Pi3k Mechanisms In Aβ42-induced Synapse Toxicitysupporting
confidence: 91%
“…Aberrant protein aggregation due to misfolding or accumulation of degraded proteins, is one of the pathological hallmarks of neurodegenerative diseases like Alzheimer's disease, Parkinson's disease, Huntington's disease, prion disease, and ALS (Brundin et al, 2010;Imarisio et al, 2008;Irwin et al, 2013;Ross and Poirier, 2004;Uddin et al, 2018;Winklhofer et al, 2008). HSP proteins have a conserved and central role in protein function by aiding in their folding and stabilization, and the clearance of misfolded proteins, ultimately diminishing protein aggregates and the associated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced exosome secretion is thought to be a compensatory mechanism in response to cellular stressors. Recent molecular studies suggest that specific molecular checkpoints, such as ATG5, ATG7, and CD63, interface with the control of exosomal release (Abdulrahman, Abdelaziz, & Schatzl, 2018;Uddin et al, 2018). Tetraspanins, a family of transmembrane proteins (e.g., CD63 and CD81) are among the most abundant surface proteins on exosomes (Booth et al, 2006;Raposo & Stoorvogel, 2013) and are often used to quantify total exosome secretion.…”
Section: Exosome Release Mechanisms In Ad and Dsmentioning
confidence: 99%
“…It was also shown that significantly more GSLs in exosomes from neurons than in those from glial cells (Yuyama & Igarashi, 2017). Since the autophagosome and other degradation pathways are disrupted in both AD and DS (Colacurcio et al, 2018;Nixon, 2017;Tramutola et al, 2016;Uddin et al, 2018), Aβ may accumulate and propagate by disrupting the normal degradation of amyloid peptides. Collective evidence strongly suggests that this is an early event, prior to the accumulation of other pathological hallmarks (Nixon, 2017).…”
Section: Exosome Cargo In Ad and Ds-admentioning
confidence: 99%